Wykluczenie cyfrowe – wybór czy konieczność? Polska na tle Unii Europejskiej - Anna Stolarczyk (Ekonomiczne Problemy Usług, 2018)
Article is focusing on the problem of digital exclusion (or digital divide) in the context of the still forming information society. In the era of the social media taking over our daily life and information and communication technologies being widely used the problem and definition of social exclusion is reforming and evolving. In this situation socially excluded groups (and governments) must struggle with new problems ahead. Autor’s starting point of the analysis of use of the internet in the households in Poland and European Union is hypothesis about correlation between social and digital exclusion.